2017
DOI: 10.1021/jacs.7b10575
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Responsive Conductive Nanofiber of Tetrabenzoporphyrin Made by Solution Processing

Abstract: While cofacial one-dimensional (1-D) π stacking of a planar aromatic molecule is ideal for the construction of conduction systems, such molecules, including tetrabenzoporphyrin (BP), prefer to form edge-to-face stacking through CH-π interactions. We report here that the BP molecules spontaneously form a 1-D cofacial stack in chloroform containing 1% trifluoroacetic acid (TFA) and that a bundle of the formed nanofiber shows acid-responsive 1-D conductivity as high as 1904 S m. A small fraction (2.7%) of BP in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…17 Linear-shaped molecules with a low H/C ratio or large aromatic systems with a high surface-to-circumference ratio generally adopt offset face-to-face arrangement since C-H$$$p interactions are insufficient to stabilize edge-to-face stacking. 8 In particular cases such as electron donor-acceptor (D-A) pairs or radical p-stacking systems, [24][25][26][27] parallel face-to-face stacking can be achieved, which is beneficial for a one-dimensional packing motif. The p-p contacts associated with face-to-face stacking are almost in the range of 3.2~3.8 Å , which is an important index revealing the strength of p-p interactions.…”
Section: Hydrogen Bondmentioning
confidence: 99%
“…17 Linear-shaped molecules with a low H/C ratio or large aromatic systems with a high surface-to-circumference ratio generally adopt offset face-to-face arrangement since C-H$$$p interactions are insufficient to stabilize edge-to-face stacking. 8 In particular cases such as electron donor-acceptor (D-A) pairs or radical p-stacking systems, [24][25][26][27] parallel face-to-face stacking can be achieved, which is beneficial for a one-dimensional packing motif. The p-p contacts associated with face-to-face stacking are almost in the range of 3.2~3.8 Å , which is an important index revealing the strength of p-p interactions.…”
Section: Hydrogen Bondmentioning
confidence: 99%
“…To confirm the integrity of the TPCP structure under different protonation degrees, FT-IR measurements were conducted and there were no new characteristic peaks observed (Supporting Information Figure S6), indicating that the TPCP structure had not undergone degradation and that it had retained its initial structure. Therefore, protonation-assisted dissolution can be attributed to the protonation of porphyrin segments in the TPCP [23,24] and the electrostatic repulsion effect.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that TTCTTC and TTTCTTTC possess high HOMO energy levels, we investigated their absorption spectra aer oxidation. It was reported that electron donors with high HOMO energy levels such as N-N linked bicarbazole or biacridine derivatives, 17 and tetrabenzoporphyrin, 18 can be oxidized by acids such CF 3 COOH. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%